The role of trust on usage intention towards mobile banking in Malaysia / Teo Pik Qi - Teo, Pik Qi (2013)
The emergence of mobile banking in recent years has brought self service banking to another level. Mobile banking enables customers to access to their banking accounts via their mobile device anytime and anywhere. However, research statistics from Bank Negara Malaysia revealed the slow growth and low subscription rate of mobile banking by customers. This research was carried out to identify the key success factors of mobile banking in Malaysia. These are the factors that impact the usage intention of customer in using mobile banking service. The aim of this research is also to investigate the mediating role of trust in the inter relationship of the key success factors and customers’ usage intention towards mobile banking in Malaysia. The research framework for this study was adapted from DeLone and McLean IS success factors model. The proposed framework was further integrated with trust as a mediator and added with another key success factor namely interface design quality. Quantitative research was applied in this study. Questionnaires were sent out manually and also via online method in order to gather the data from mass Malaysian population. The data were analyzed using multiple regression and Sobel test for mediation effect. The findings of this study demonstrated the proposed framework whereby trust played a significant mediating role on the effect of system quality, information quality and interface design quality on customers’ usage intention. The results also revealed the significance of impact for three key success factors mentioned in the study.